Knowledge, Attitude and Practice Regarding Menstrual Hygiene among Women of Reproductive Age in Duhabi, Sunsari - Dhital, Aachal; Rijal, Amrit; Niroula, Arpan; Adhikari, Nishan; Adhikari, Bigyan; Adhikari , Sneha (Journal of Nobel Medical College, 2025)
Background: Menstrual hygiene remains a public health concern in Nepal, particularly in rural areas where cultural restrictions, limited awareness, and inadequate access to menstrual products influence women’s practices. Existing studies predominantly focus on adolescents, leaving gaps in understanding menstrual hygiene among the wider reproductive-age population. This study assessed the knowledge, attitudes, and practices regarding menstrual hygiene among women of reproductive age in Duhabi, Sunsari. Materials and Methods: A descriptive cross-sectional study was conducted from April to August 2024 among 102 women aged 15–49 years in Ward No. 11 of Duhabi Municipality. Participants were selected through convenience sampling. Data were collected using a structured, interviewer-based questionnaire covering socio-demographic characteristics and menstrual hygiene related knowledge, attitudes, and practices. Ethical approval and written informed consent were obtained. Descriptive statistics were analyzed using SPSS version 29. Results: A total of 102 women of reproductive age (15 to 49 yrs) were analyzed. Knowledge assessment showed that 58.8% of participants recognized disposable sanitary pads as the best absorbent, while 41.2% believed in cloth. Most women (89.2%) believed that poor menstrual hygiene could lead to health issues, identifying problems like infections (4.9%) and diseases related to the uterus (35.3%). Cultural restrictions were prevalent, with 79.4% avoiding religious activities during menstruation. Daily bathing (93.1%) and genital cleaning (100%) were widely practiced. The majority (62.7%) had frequent changing habits of absorbents, while the infrequency of changing habits, reported by 37.3% of respondents, indicates a significant knowledge gap. Conclusion: The findings show a combination of appropriate and suboptimal menstrual hygiene practices among women in Duhabi. Despite basic awareness of hygiene, significant gaps persist in absorbent choice, frequency of changing, and culturally influenced restrictions. These patterns reflect how economic limitations and cultural beliefs shape menstrual hygiene behaviors in this rural community.